Variability of cost and return of dry direct seeded lowland rice in major rainfed growing areas in the Philippines - Ocampo, Oliver C.; Makahiya, Hazel Anne F.; Pamplona, Marjorie V.; Motilla, John Kenneth L.; Banayo, Niño Paul Meynard C.; Bueno, Crisanta S.; Sta. Cruz, Pompe C. (2023)
This study was conducted to evaluate the variability of net income and return on investment (ROI) as affected by grain yield, cost of production, and gross income across provinces wherein the mechanized dry direct seeding technology was being deployed. The study was conducted during 2019 wet season involving 54 sites from 14 provinces with farmers practicing mechanized dry direct seeding technology under rainfed lowland condition. Grain yield varied (0.72 – 6.73 t ha-1) across provinces and within each province. Total cost of production varied (PhP 23032 – 43421 ha-1) across provinces. Most sites in Cagayan had high cost of production while low in Negros Occidental. Fertilizer cost was the major expense of more than 50% of rice farmers across provinces. Gross income ranged from PhP 32939 ha-1 (South Cotabato) to PhP 73873 ha-1 (Abra). Highest net income was obtained in Sultan Kudarat due to high yields. Net income was less variable in Ilocos Sur while highly variable in South Cotabato. The return on investment (ROI) of different provinces varied (71.61 ± 62.63%). Low ROI and less variability were noted in Ilocos Norte, Ilocos Sur, and La Union. Across provinces, 60.7% of total variation was explained by variations in grain yield. About 50% of variations in ROI was associated with cost due to land preparation and pesticide application. Fertilizer cost accounted for the high ROI in Abra and Antique. The cost of harvesting significantly affected ROI in Albay, Antique, Cagayan, Camarines Sur, Ilocos Norte, Ilocos Sur, and South Cotabato. In general, variability in ROI across provinces were affected by grain yield levels, or the total or the specific items in the cost of production, which is site or province specific. From the information generated, interventions can be formulated based on identified limiting factors specific to site or province.
Keywords: Agricultural income; Rice production; Seeding